2022
DOI: 10.3390/foods11162525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seaweeds on the Quality of Pasta as a Plant-Based Innovative Food

Abstract: This study evaluated the effect of the incorporation of seaweed on the physicochemical and technological quality of pasta. For this purpose, enriched wheat pastas from different seaweeds (sea lettuce—Ulva lactuca, nori—Porphyra tenera, and wakame—Undaria pinnatifida) were made and compared with durum wheat pasta as a control treatment. Firstly, optimal cooking times were established by visual and instrumental methods. Then, the technological properties of weight gain (WG), swelling index (SI), cooking losses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
8
2
Order By: Relevance
“…In the previous studies it was also documented that supplementation of pasta with plant sources and aquatic sources such as microalgae and seafern significantly enhanced the nutritional value of pasta (Batista et al, 2017;Lafarga, 2019;Bawa et al, 2022). Ainsa et al (2022) in their study, however, reported that addition of different seaferns (at 3%) in pasta improved its protein and fibre content; however, in present study addition of Azolla beyond 5% level improved the nutritional quality of pasta. quality.…”
Section: Proximate Composition and Mineral Contentcontrasting
confidence: 45%
See 3 more Smart Citations
“…In the previous studies it was also documented that supplementation of pasta with plant sources and aquatic sources such as microalgae and seafern significantly enhanced the nutritional value of pasta (Batista et al, 2017;Lafarga, 2019;Bawa et al, 2022). Ainsa et al (2022) in their study, however, reported that addition of different seaferns (at 3%) in pasta improved its protein and fibre content; however, in present study addition of Azolla beyond 5% level improved the nutritional quality of pasta. quality.…”
Section: Proximate Composition and Mineral Contentcontrasting
confidence: 45%
“…Furthermore, increase in the fibre content provide the pasta with the stiff structure as a result of which pasta showed a higher firmness than control (Bianchi et al, 2021). On the contrary, Ainsa et al (2022) reported that addition of different seaweed at 3% level results in decreasing the hardness value of pasta due to weakening of the pasta dough structure by addition of non-gluten protein and fibre rich ingredient.…”
Section: Colour Characteristics and Textural Firmnessmentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, researchers have developed pasta with various bioactive ingredients, such as: Moringa oleifera pod powder [ 168 ]; Purslane [ 172 ]; Soy okara [ 167 ]; Stinging nettle [ 169 ]; Fermented quinoa flour [ 170 ]; Potato and pigeonpea flour [ 178 ]. Carrob flour [ 176 ] Mushroom powder [ 171 , 180 ]; Brewers spent grain [ 173 , 174 ]; Carrot waste encapsulates [ 177 ]; Olive pomace [ 179 ]; Fish raw material [ 165 ]; Micro and macroalgae [ 166 , 175 , 181 , 182 , 183 , 184 ]. …”
Section: Resultsmentioning
confidence: 99%